How Russia’s war in Ukraine can change gender studies - Johnson, Janet Elise (Frontiers in Sociology, 2023)
The catastrophe of Russia’s war in Ukraine following on the heels of the COVID-19 pandemic and the Black Lives Matter-inspired protests raises the possibility of marked changes in people’s gendered experiences in Central-Eastern Europe and Eurasia (CEE&E). Drawing upon recent discussions, events, and publications—with particular attention to Ukrainian voices and reflexivity as to my position as a US-based political scientist mostly trained on Russia—I suggest ways that these developments have begun to, can, and should change gender studies. I raise three questions: (1) Does CEE&E still constitute a meaningful geopolitical context—or region—for understanding gender? (2) Who should have authority to speak about gender in CEE&E? and (3) Have the possibilities for solidarities among feminist activists across CEE&E and beyond CEE&E increased or decreased, and why? Considering these questions, I argue that there is still much to be gained from studying gender in CEE&E as a field if we incorporate intersectional and decolonial lenses and especially if we can keep pushing ourselves through the scholarly debates that have constituted the field. Incorporating this part of the world—elided since Soviet collapse—can help gender studies as a whole deepen and reconsider paradigmatic concepts such as intersectionality, colonialism, and solidarity.